What we really value : beyond rubrics in teaching and assessing writing - Broad, Bob, 1960- (Utah State University Press, 2003)
The result of a long-term study of one university's introductory composition program, Broad's approach to mapping the values that inform writing evaluation is empirically grounded, painstakingly analyzed, yet flexible, human, and pedagogically wise. Not simple, but surely practical, his method yields a more satisfactory process of exploration and a more useful representation of the values by which compositionists actually evaluate their students. With this important study, Broad moves the field far beyond rubrics in teaching and assessing writing.